Death due to Intracranial Penetrating Stab Wounds Case Report - Alper, Benhan; Gülmen, Mete Korkut; Çekin, Necmi; Bilgin, Nursel; Salaçin, Serpil (The Bulletin of Legal Medicine, 1999)
Previous studies performed by our team showed that stabbing is the leading cause of homicides in Adana city. It is believed that patients with multiple injuries have the worst prognosis and also suggested that stabbing wounds on the head have a very low risk of injury. We report four unusual stabbing cases showing intracranial penetration because of rareness in the literature. Key words: Wounds, Stab wounds, Medicolegal autopsy, Penetrating wounds of head.